2000
DOI: 10.1097/00003246-200009000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of nosocomial bloodstream infections: Effectiveness of antimicrobial-impregnated and heparin-bonded central venous catheters

Abstract: The modest additional cost for the use of these catheters relative to the considerable cost of treating even a single bloodstream infection makes their use cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 15 publications
2
36
0
3
Order By: Relevance
“…[2][3][4][5][6][7] A summary of these reviews is presented in Appendix 1 and the conclusions drawn by each of the reviews are shown in Table 4.…”
Section: Previous Reviews Of Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…[2][3][4][5][6][7] A summary of these reviews is presented in Appendix 1 and the conclusions drawn by each of the reviews are shown in Table 4.…”
Section: Previous Reviews Of Effectivenessmentioning
confidence: 99%
“…The literature search highlighted 13 review articles. [2][3][4][5][6][7]40,[101][102][103][104][105][106] Six of these reviews were systematic reviews of the clinical effectiveness of antimicrobial impregnated/coated CVCs. [2][3][4][5][6][7] The reasons for exclusion of the remaining seven reviews are shown in Table 25.…”
Section: Contribution Of Authorsmentioning
confidence: 99%
See 3 more Smart Citations